Unusual manifestation of isolated cutaneous toxoplasmosis in an immunocompetent patient - Shirish Nandedkar; Trupti Bajpai; Kamal Malukani; Ganesh S Bhatambare (Wolters Kluwer Medknow Publications, 2015)
A rare and probably the first documented case of isolated cutaneous toxoplasmosis is being reported in a 50-year-old, vegetarian, immunocompetent man. The granulomatous nodule located on the scrotal skin was excised, and the sections and crushed material of the nodule were subjected to different staining techniques. Demonstration of crescentic structures and PAS-positive material confirmed the presence of Toxoplasma gondii. The significantly raised titer of anti-toxoplasma antibodies further supported the diagnosis. The case was successfully managed surgically. No further treatment was advised since the patient was immunocompetent and it was assumed that cell-mediated immunity would further control the proliferation of organisms.